Existentialism in Sufism: A Sociological Analysis of Bhitai's Thoughts - Sandeelo, Naveed Hussain; Naich, Moula Bux; Daudpota, Rashid Ali (Annals of Human and Social Sciences, 2023)
This paper examined Bhitai's thoughts as a Sufi poet, despite the fact that little has been written about Existentialism in Sufism. It is mostly based on the supposition that his followers accumulated after his death. Even Literary scholars have yet to make tangible and analytical comments on his poems. Therefore, exploring the depths of Bhitai's Sufi thought and its existential foundations through his poetry would require someone who has not only been initiated into Sufism but also ventured quite far into the mysterious world of mysticism. To investigate the relevance of Sufi philosophy in the modern era while being conscious of his extremely limited knowledge in the field. To emphasize the theologians' antagonistic attitude toward the mystics and to recreate the historical circumstances in the subcontinent in the seventeenth century. The findings of this study proved valuable to individuals who have a direct or indirect connection to Bhitai's poetic ideas or existential themes. By analyzing Bhitai's poetic ideas, it becomes evident that the poet's main objective was to bring about significant transformation in an outdated society.